Optimization of Gel Cream Containing HAMIN™ and HPMC K100M as Bases for Topical Delivery of Diclofenac Sodium - Lina Winarti; Amirah Mohd Gazzali; Fania Mufti Mufidah; Fahrauk Faramayuda; Evi Umayah Ulfa; Dwi Nurahmanto; Muhammad Hilmi Afthoni; Liza Pratiwi; Bambang Wijianto (Borneo Journal of Pharmacy, 2026)
Diclofenac sodium, a widely used NSAID, has limited skin permeability, which reduces its topical efficacy; therefore, a gel-cream formulation combining the rapid absorption of gels with the emollient properties of creams is proposed to enhance drug penetration and patient comfort. To further improve delivery, HAMIN™, a novel natural palm oil–based base with excellent biocompatibility and lipid-enhancing properties, will be combined with HPMC K100M. This thickener stabilises viscosity and prolongs skin contact time, supporting better absorption. This study aimed to develop and optimise a topical gel cream for diclofenac sodium using HAMIN™ and HPMC K100M to achieve ideal physical properties and improved skin penetration. The formulation was statistically optimised using a Simplex Lattice Design (SLD), with HAMIN™ (X1) and HPMC K100M (X2) as independent variables, and pH (Y1), spreadability (Y2), viscosity (Y3), extrudability (Y4), release flux (Y5), and permeation flux (Y6) as dependent responses. Optimisation with Design Expert version 13 yielded the ideal composition of 16.84% HAMIN™ and 1.16% HPMC K100M, resulting in predicted values of pH 5.07, spreadability 7 cm, viscosity 4502.25 mPas, extrudability 78.98 N/s, release flux 70.61 µg/cm2/minute, and permeation flux 0.4868 µg/cm2/minute, with a desirability score of 0.829. Despite a slightly lower release flux, the optimised HAMIN™ and HPMC K100M-based gel cream demonstrated superior skin permeation compared to a commercial emulgel for up to 300 minutes. The incorporation of HAMIN™, a natural palm oil base, offers a novel and effective strategy to enhance the topical delivery of diclofenac sodium via a statistically optimised gel cream formulation.